The Impact of the Zonation System on the Competence of PAI Teachers at SMAN 10 Padang - Yahya, Zaini Aulia; Wirdati, Wirdati (Lembaga Yasin AlSys, 2023)
This study focuses on the impact of the zoning system on the competence of Islamic Religious Education teachers at SMAN 10 Padang. The purpose of this research is to find out whether the zoning system has an impact on the competence of PAI teachers at SMAN 10 Padang. Zoning is one of the policies stipulated by the Ministry of Education and Culture in the context of efforts to equalize access to quality education, and in its application, it has had many impacts, starting from public confusion about the zoning system due to lack of socialization, lack of transparency and accountability, even to the stuttering of educators in dealing with the implementation of the zoning system. this. This research is qualitative research with a descriptive method that will describe the impact of the zoning system on the competence of PAI teachers at SMAN 10 Padang. The results of this study are that the application of the zoning system has an impact on the competence of PAI teachers both in pedagogical competence, social competence, personal competence, and professional competence.